Technostress and Smartphone addiction mediated by Smartphone distraction in college students - Vallejos-Flores, Miguel (2024)
Introduction: the development of academic activities through virtual spaces contributes to increasing the use of Smartphones in university students, arising the need to study the effects of their use. Objective: to evaluate the mediating effect of Smartphone distraction between technostress and Smartphone addiction in university students in Metropolitan Lima. Methods: A sample of 550 university students, aged between 18 and 35 years, was evaluated with the Smartphone Distraction Scale, the Technostress Scale for University Students and the Smartphone App-Based Addiction Scale. Regression analysis was conducted to assess the mediating role of smartphone distraction in the explanatory relationship between technostress and cell phone addiction. Results: a complete effect on the part of the mediator was identified, in addition, it is observed that there is an indirect effect of technostress on smartphone addiction. Discussion: smartphone distraction has an effect on cell phone addiction as long as distraction is present as a mediator.